The Impact of Learning Styles and Teaching Styles on Second Language Learning Success - Lovely Jane L. Balonda; Lawrence Anthony U. Dollente (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: Individuals learn in unique ways, influenced by their preferences, ethnic backgrounds, cultures, and personal experiences. Similarly, teaching styles are shaped by educational philosophies and subject matter, leading to potential mismatches in how knowledge is processed in the classroom. This study aimed to identify the learning and teaching styles of students and teachers, explore the alignment between them, and assess the implications for language teaching. Methodology: This descriptive quantitative study involved 166 students and 23 teachers from the Department of English Language and Literature (DELL) at the University of Southern Mindanao. Data were collected using the Strategies Questionnaires and the VARK Questionnaire for Trainers to assess learning and teaching styles. Main Findings: The study revealed that AB English Language (ABEL) students predominantly exhibited bimodal learning preferences, particularly in the aural-read/write (AR) and aural-kinesthetic (AK) modalities. DELL teachers, on the other hand, tended to favor single-modal teaching styles, with a slight visual preference. A strong match was observed between single-modal teachers and students with similar learning preferences, although kinesthetic learning was underrepresented. Teachers who were bimodal or trimodal showed a better alignment with a wider range of student learning preferences. Additionally, all-modal teachers demonstrated the most effective alignment across all VARK learning styles. Novelty/Originality of this study: This study introduces a fresh perspective on language instruction by emphasizing the importance of incorporating multiple teaching styles to match the diverse learning preferences of students. The findings suggest that creating course outlines with a variety of teaching styles is essential for fostering more effective and inclusive language learning environments, ultimately enhancing student engagement and success.